PENGGUNAAN RINFOCAL SEBAGAI APLIKASI PENGINGAT (REMINDER) KEGIATAN AKADEMIK PADA PERGURUAN TINGGI - Indri Handayani; Qurotul Aini; Yessy Oktavyanti (Universitas Raharja, 2015)
Progress of technology and its developed is going so rapidly nowadays and it provide big affect on human life, some of them were education and daily life. Due to its development we also know the other form of calendar which is in digital form that we usually found in gadgets such as handphone or tablets and surely it is portable. Rinfo which is an email supporting facilities for the needs of Raharja College may help Pribadi Raharja in coordination and communication about task and/or event. Rinfo has some applications that integrated with Rinfo itself, such as RinfoGroup, RinfoSites, RinfoDocs, RinfoDrive, RinfoH and RinfoCal. RinfoCal is an calendar application that can be use as schedule time reminder application and it will send any reminder not only to one person but some or couple persons. RinfoCal may sent an pop-up notification or email notification. This paper will discuss about what is RinfoCal, how to use it, what’s the purpose of using RinfoCal, benefit of RinfoCal and so on. But, instead of its benefit, there are also some shortages including many people who using Rinfo doesn’t get the benefit of RinfoCal because they just pretending that RinfoCal is just an usual calendar. This paper also present six problems from conventional reminder that will solved by RinfoCal fews are just doing reminders only once at a time or just remembering only one person, a mind mapping to simplify the analyze of problem and make the best solution, eight literature reviews that had been done to help analyzing problems of research.